Nurse Caring Attitude Relationships with Parents Patient Satisfaction Level in Public Hospitals Pambalah Batung Amuntai - Tasalim, Rian; Basit, Mohammad; Agustina, Rita (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
Caring is a form of nurse's concern for clients. Nurses are required to have the sensitivity and ability to support the trust and well-being of patients. Patient/Parent satisfaction is highly dependent on the caring attitude of the nurse. The better the caring attitude of the nurse to the patient, the more the patient will trust the nurse. Nurse caring behavior is one of the determinants of patient satisfaction. The purpose of this study was to determine the relationship between the caring attitude of nurses and the level of satisfaction of the patient's parents in the pediatric ward of Pambalah Batung Amuntai Hospital. Analytic research with a cross sectional approach. Collecting data using a questionnaire. Respondents in the study amounted to 28 people, using probability sampling technique. Data analysis using Chi-Square. The results show that in the pediatric ward of Pambalah Batung Amuntai Hospital, it is known that the caring attitude of nurses in the classification is not good, namely 68% and the level of satisfaction of parents of patients in the less classification is also as much as 64 % The results of the Chi-Square analysis obtained a significant value of 0.019 (p < 0.05). There is a relationship between the caring attitude of nurses and the level of satisfaction of parents whose children are cared for in the pediatric care room at Pambalah Batung Amuntai Hospital.